Implementasi Program Gema Sajadah (Gerakan Madrasah Sampah Jadi Sedekah) dalam Membentuk Karakter Peduli Lingkungan Siswa di MTsN 9 Jombang - Aini, Aizzatun Nur; Syamsuddin, H. (Lembaga Yasin AlSys, 2025)
The Gema Sajadah Program (Gerakan Madrasah Sampah Jadi Sedekah) is an environmentally based initiative aimed at developing students' environmentally conscious character through waste management activities and social actions. The issue raised in this study is the lack of student involvement in concrete environmental conservation activities within the school environment. This study aims to determine the implementation of the Gema Sajadah Program, identify students' environmentally conscious character, and examine the program's influence on character formation in students at MTsN 9 Jombang. The method used is a qualitative approach with a case study design, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that this program significantly fosters awareness and an environmentally caring attitude among students. Through direct practice, such as collecting recyclable waste and used cooking oil, students demonstrate an increase in concern for cleanliness and environmental sustainability. Social interaction during these activities also strengthens empathy and collective responsibility. In conclusion, Gema Sajadah is effective in shaping students' character through an applicable contextual approach. Its implication is that this program can serve as a character education model that can be replicated in other schools as an effort to cultivate a generation that is balanced in its concern for environmental and social issues.